2013
DOI: 10.5539/elt.v6n6p113
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Consciousness-Raising Tasks in Learning and Teaching of Subject-Verb Agreement

Abstract: This study investigates the use of two types of Consciousness-Raising (CR) tasks in learning Subject-Verb Agreement (SVA). The sample consisted of 28 Form 2 students who were divided into two groups. Group 1 was assigned with Grammaticality Judgment (GJ) tasks and Group 2 received Sentence Production (SP) tasks for eight weeks. Learners were given a pretest before the treatment and a posttest once they completed the tasks. They were also required to answer questionnaires and some were interviewed. The findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…This characteristic was included in step 1 of the CRTs, where the students had to articulate the rule after having analyzed the input. According to Idek, Fong and Sidhu (2013), operational skills, collaboration with peers, and explicit instruction may contribute to students' understanding of the grammar feature. Therefore, after the interventions were carried out, the researchers concluded that more attention should have been given to the students in articulating the rule at the end of the CRTs.…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic was included in step 1 of the CRTs, where the students had to articulate the rule after having analyzed the input. According to Idek, Fong and Sidhu (2013), operational skills, collaboration with peers, and explicit instruction may contribute to students' understanding of the grammar feature. Therefore, after the interventions were carried out, the researchers concluded that more attention should have been given to the students in articulating the rule at the end of the CRTs.…”
Section: Discussionmentioning
confidence: 99%
“…Above all, it endorses learners' awareness of the target form, which as stated by Schmidt (1990) is the earlier and indispensable phase of learning. Schmidt (1990) believes that before learners can learn anything, they have to be aware of first of what they are learning, pay attention to it, and notice it (Idek, Fong, & Sidhu, 2013).…”
Section: Consciousness-raising (Cr)mentioning
confidence: 99%
“…Dictogloss demands learners to comprehend the message of the original text, identify important points, exercising different cognitive processes of solving the tasks (matching, ordering and listing), use their knowledge of the target language to recreate the texts in a different version, identify the verbs, tap into their knowledge of grammar to alter the verbs into their past tense forms, compare their text with another version, analyze their errors and any other skills pertinent to the tasks. Idek (2014) stated that demanding tasks can push learners to become cognitively involved in active processing the target forms as well as routinize the operations needed in dealing with particular grammatical forms that assist learners to become competent in using the target forms. In addition, the requirement for learners to compare their texts and analyzed their errors also helped them to develop explicit knowledge of the target forms (Widodo, 2006) as it enables them to construct and confirm their hypothesis of how the target form is applied (Mull, 2013).…”
Section: Journal Of Management Researchmentioning
confidence: 99%